Luftslott och andra fantasier - Ehn, Billy (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2005)
Fantasies are a marvellous tool for escape and freedom. Social life is unthinkable without imagination. It both creates gulfs and bridges them. The conversation on the telephone relies upon guesswork by the listeners. Using very slight data we jump to quite unjustified conclusions about people. On the other hand misunderstandings may be quite creative interpretations of what they think. The distinction between the world outside and the world of imagination is by no means obvious. This article presents several examples of how everyday fantasies can be used in the cultural analysis of, for example, the home, different professions and the politics. With "ethnography from the corner of the eye" we will see the imaginative potentials of social life in a new perspective.